ANALISIS AKTIVITAS ANTIOKSIDAN DAN KANDUNGAN ANTOSIANIN TOTAL EKSTRAK DAN LIPOSOM KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa L.) - , I Gede Agus Juniarka ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Roselle (Hibiscus Sabdariffa L.) calyxeses extract was known as a natural antioxidant related to its anthocyanin content. Anthocyanin has low stability, it easy to reduce caused by environmental factors. Liposome formulation is one of the alternative to increase the stability of anthocyanin in roselle extract. Beside that, due to the liposome layer it may reduce the irritation of extract. So that, in this research we analyze the stability of antioxidant activity and total anthocyanin content, also dermal toxicity of extract and liposome derived from roselle calyxes. Anthocyanin extraction is carried out by the maceration. The optimal solven for anthocyanin extraction of roselle calyxes is methanol : formic acid (97:3). The rendement was 26.40% w/w and its antioxidant activity (DPPH testing of 20Î¼L extract) was 19.99% (+ 0.001). The obtained IC50 values of methanol extract of roselle petals 16.59 (+ 0.06) mg/mL. The antioxidant activity of roselle calyxes extract correlated to total anthocyanin content (R2 = 0.9253), however there are other substances that support the antioxidant activity of roselle calyxes extract. For that reason, comparison analysis in this research not only by total anthocyanin content, but also by the antioxidant activity. Liposome formulations of methanol extract from roselle petals prepared by reverse phase method. The stability study show that there was a reduction of antioxidant activity 11.25 % for the roselle extract, while the liposome form was 0.93% after 30 days storage in low temperature (0-50C) saturated nitrogen. So does the total anthocyanin content, there was a reduction 39.12 % for the roselle extract and 0.72% for the liposome form. More over, less irritation observed in the anthocyanin extract encapsulated by liposome. For that reason, anthocyanin encapsulated by liposome more stable, safe, and effective compared to the roselle calyxes extract